ISO 37120 e Objetivo do Desenvolvimento Sustentável 11: convergência frente à Agenda 2030 - Ribeiro, Tatiana Soares Viana (2019)
Cities are in constant growth and no longer hold the current population due to administrative, social and economic factors, generating a lack of organization and basic structures, such as sanitation, quality transportation, poverty, hunger, among others. lack of effective public policies. This growth of the population agglomerates brings social inequality between the inhabitants and poor quality of life. Thinking about the next generations and aiming to improve people's lives in order to provide the inhabitants with a sustainable city for all, international bodies such as the United Nations (UN) and ISO (International Organization Standardization) have developed objectives and indicators public management of cities, both with the objective of meeting Agenda 2030 established by the UN. The research in question analyzed the particularities of each city indicator (ISO 37120) and the Sustainable Development Goals 11 (SDG11) and their correlations, noting the benefits they will bring to make cities sustainable. According to the literature, governance and decision makers should implement more adequate public policies, based on the results of the indicators, observing improvements and best practices. The analyzes led to interactions between both standards and those that were not related to ISO 37120 or SDG11 related to other SDG, complementing the indicators of both Standards. In the research, both indicators converge and complete, making the indicators more complete among them, and bringing specific observations to improve the quality of life in cities. In case of joining ISO 37120 and SDG 11, decision makers and / or governance will have access to more complete and more adequate indicators for the reality of each city.